Mentoring Matters: Preservice Teachers’ Perceptions of Mentor Teachers’ Competencies in the Practicum - Yılmaz Yıldız, Seval Bircan; Girgin, Derya; Satmaz, İsmail and Kiraz, Ercan (Journal of Qualitative Research in Education, 2025)
This study explores preservice teachers’ perceptions of what defines a qualified cooperating teacher in the teaching practicum. Adopting a phenomenological design, data were collected from 150 prospective teachers across multiple subject areas at a public university in Türkiye through semi-structured interviews. The data were analyzed using content and discourse analysis supported by MAXQDA. Findings show that preservice teachers identify communication, guidance and feedback, professional knowledge and planning, role modelling, and motivation as key qualities of a qualified cooperating teacher. Discourse analysis revealed recurring patterns of guidance, collegiality, support, and neglect, illustrating how practicum contexts construct power relations and identity recognition. Constructive feedback, collegial mentoring, and role modelling were viewed as most influential for professional growth, whereas inadequate communication, weak feedback, and authoritarian attitudes hindered development. By centering preservice teachers’ voices, the study contributes to teacher education and proposes a multidimensional framework for redefining the role of cooperating teachers in teacher preparation.